Nitrogen flux and hydrochemical characteristics of the calcareous aquifer of the Zana plain, north east of Algeria, July, ISSN /e- ISSN: 1866-7511 / 1866-7538 - ATHAMENA Ali; MENANI Mohamed redha (Arabian Journal of Geosciences, 2018)
The hydrochemical and multivariate statistical techniques such as the principal component analysis (PCA) and the cluster analysis (CA) were used to identify the hydrochemical processes and their relation with groundwater quality and also to get an insight into the hydrochemical Zana aquifer groundwater chemistry evaluation. Twenty-four samples during the wet season and even during the dry season are analyzed. The Piper diagram showed that water facies are magnesium bicarbonate on the sides of the western reliefs and magnesium chloride-sulfated at the north and the center of the plain. The PCA carried out on three factors revealed that on the factorial design F1-F3, nitrates negatively determine factor 3, indicating the presence of an agriculture pollution. On the factorial design F1-F2, HCO3− positively determine the factor 2, indicating the carbonated origin. However, the CA, based on variables, showed that the waters in the region can be classified into three groups according to flow direction while the CA, based on major ion contents, defined three groups, reflecting the same hydrochemical facies. The first group with dry residue varying between 360 and 1700 mg/l and characterized by Mg2+ and Cl−, HCO3−. Samples of this group are mostly located in the north and northeastern part of the region. The second group with highest dry residue (2080 to 3820 mg/l) characterized by Mg2+ and SO4−, Cl− is located near the Northwestern and western outcrops. The third group coincides with the central part, the lowest of the plain, with heightened dry residue (4140 to 13,950 mg/l), characterized by Mg2+ and SO4−. The hydrochemical study made it possible to allot the evaporitic origin to the elements Na+, Mg2+, K+, Cl−, and SO4−, while for element HCO3−, it results from the carbonated formations. These results showed that the presence of nitrates in the studied area is closely linked to the agricultural activity.